Integrated Geodetic and Hydrographic Measurements of the Yacht Port for Nautical Charts and Dynamic Spatial Presentation - Makar, Artur; Specht, Cezary; Specht, Mariusz; Dąbrowski, Paweł; Szafran, Maciej (Geosciences (Basel), 2020)
The use of geodetic and hydrographic systems, methods and measuring devices to obtain geospatial data enables integrated modeling of 3D space and related objects. Factors such as the seafloor relief of the marina and land infrastructure need to be considered to ensure safe stay of vessels in the marina. The article presents the results of bathymetric and geodetic measurements of the yacht port of the National Sailing Centre in Gdańsk. They were made with the use of several measuring methods such as a hydrographic unmanned surface vessel, GNSS positioning, enabling geodetic inventory of hydrotechnical structures and port infrastructure, as well as laser scanning that resulted in three-dimensional presentation of land objects. As a result of research and analysis, a two-dimensional bathymetric chart of the yacht port was made. Thanks to the integration of geodetic and hydrographic data, three-dimensional visualization of the marina area was obtained. The charts can be used to ensure ship navigation safety when maneuvering in port and mooring at quays.